2016
DOI: 10.1259/bjr.20150911
|View full text |Cite
|
Sign up to set email alerts
|

Palatal lesions: discriminative value of conventional MRI and diffusion weighted imaging

Abstract: Objective: To evaluate and compare the ability of conventional MRI, diffusion-weighted imaging (DWI) and a combination of both MRI techniques to differentiate malignant and benign palatal lesions. Methods: A retrospective review of MRI findings was performed in patients with pathologically confirmed palatal lesions between January 2012 and December 2014. Each lesion was evaluated with conventional MRI characteristics, including enhancement, inner texture, margin, adjacent soft-tissue involvement and cervical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Conventional magnetic resonance imaging (MRI) plays an important role in delineating the extent of palatal lesions and identifying perineural spread as well as spread to lymph nodes because of its superior soft tissue resolution, 1,7 thereby complementing clinical examination. Although diffusion weighted imaging (DWI) and other advanced MR approaches have been used to assess palatal tumors, 8,9 Yuan et al 9 noted that DWI did not dramatically improve the ability of conventional MRI to differentiate between benign and malignant palatal lesions, indicating that routine MRI remains the mainstay imaging modality in the palate.…”
mentioning
confidence: 99%
“…Conventional magnetic resonance imaging (MRI) plays an important role in delineating the extent of palatal lesions and identifying perineural spread as well as spread to lymph nodes because of its superior soft tissue resolution, 1,7 thereby complementing clinical examination. Although diffusion weighted imaging (DWI) and other advanced MR approaches have been used to assess palatal tumors, 8,9 Yuan et al 9 noted that DWI did not dramatically improve the ability of conventional MRI to differentiate between benign and malignant palatal lesions, indicating that routine MRI remains the mainstay imaging modality in the palate.…”
mentioning
confidence: 99%
“…Ishii et al 2 showed that the internal echo pattern on the ultrasonogram of a palatal tumor was found to reflect the pathologic structure of the tumor. On DWI, Yuan et al 4 showed that the optimal cut‐off ADC value to distinguish malignant from benign lesions was 1.02 × 10 −3 mm 2 s −1 , with a sensitivity of 87.5% and a specificity of 75.0%. In this study, the mean ADC value of squamous cell carcinoma (1.10 ± 0.11 × 10 −3 mm 2 s −1 ) was significantly lower than that of pleomorphic adenoma (1.49 ± 0.41 × 10 −3 mm 2 s −1 , P = .046) and another benign tumor (1.85 ± 0.40 × 10 −3 mm 2 s −1 , P = .000).…”
Section: Discussionmentioning
confidence: 99%
“…We consider that our results were preliminary study, and further research is necessary to validate these results. Yuan et al 4 showed DWI in 42 patients with palatal lesions. Oda et al 8 indicated DWI in 57 oral and maxillofacial lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In general, lesions and tumours with high cellularity or cellular swelling tend to present lower apparent diffusion coefficients (ADCs). Accordingly, ADC values have been reported to be lower in malignant tumours, as compared with benign tumours, [6][7][8] and inflammatory lesions. 9 For alterations of the salivary glands, MRI might be decisive for the diagnosis and can also contribute to defining the stage of the disease.…”
Section: Introductionmentioning
confidence: 99%